Impact of the caller's emotional state and cooperation on out-of-hospital cardiac arrest recognition and dispatcher-assisted cardiopulmonary resuscitation. Issue 10 (22nd August 2019) - Chien, Cheng-Yu; Chien, Wei-Che; Tsai, Li-Heng; Tsai, Shang-Li; Chen, Chen-Bin; Seak, Chen-June; Chou, Yu-Shao; Ma, Matthew; Weng, Yi-Ming; Ng, Chip-Jin; Lin, Cheng-Yu; Tzeng, I-Shiang; et al.
Abstract : Objective: This study determined the impact of the caller's emotional state and cooperation on out-of-hospital cardiac arrest (OHCA) recognition and dispatcher-assisted cardiopulmonary resuscitation (DA-CPR) performance metrics. Methods: This was a retrospective study using data from November 2015 to October 2016 from the emergency medical service dispatching centre in northern Taiwan. Audio recordings of callers contacting the centre regarding adult patients with non-traumatic OHCA were reviewed. The reviewers assigned an emotional content and cooperation score (ECCS) to the callers. ECCS 1–3 callers were graded as cooperative and ECCS 4–5 callers as uncooperative and highly emotional. The relation between ECCS and OHCA recognition, time to key events and DA-CPR delivery were investigated. Results: Of the 367 cases, 336 (91.6%) callers were assigned ECCS 1–3 with a good inter-rater reliability ( k =0.63). Dispatchers recognised OHCA in 251 (68.4%) cases. Compared with callers with ECCS 1, callers with ECCS 2 and 3 were more likely to give unambiguous responses about the patient's breathing status (adjusted OR (AOR)=2.6, 95% CI 1.1 to 6.4), leading to a significantly higher rate of OHCA recognition (AOR=2.3, 95% CI 1.1 to 5.0). Thirty-one callers were rated uncooperative (ECCS 4–5) but had shorter median times to OHCA recognition and chest compression (29 and 122 s, respectively) compared with the cooperative caller group (38 and 170 s, respectively). Nevertheless, those with ECCS 4–5 had a significantly lower DA-CPR delivery rate (54.2% vs 85.9%) due to 'caller refused' or 'overly distraught' factors. Conclusions: The caller's high emotional state is not a barrier to OHCA recognition by dispatchers but may prevent delivery of DA-CPR instruction. However, DA-CPR instruction followed by first chest compression is possible despite the caller's emotional state if dispatchers are able to skilfully reassure the emotional callers.